Obesity management among patients with type 2 diabetes and prediabetes: a focus on lifestyle modifications and evidence of antiobesity medications. Issue 5 (3rd September 2017) - Nguyen, Bao; Clements, Jennifer
ABSTRACT: Introduction : The prevalence of obesity has increased over the past three decades in the United States and worldwide. This article reviews landmark trials for lifestyle modifications as well as clinical evidence and implications for locaserin, phentermine with topiramate, buproprion with naltrexone, and liraglutide in patients with type 2 diabetes and obesity. Areas covered : A MEDLINE search, from 1970 to May 2017, was conducted using key search terms - lifestyle modifications, antiobesity medication, obesity and diabetes. Published clinical trials, in the English language, with the adult patient population of type 2 diabetes or prediabetes, were reviewed and critiqued. Expert commentary : Lifestyle modifications have shown to prevent the progression to type 2 diabetes mellitus. Pharmacologically, each medication has proven effect on both type 2 diabetes mellitus and obesity, specifically reducing weight from baseline by 4.7 kg, 10.2 kg, 5.0 kg, and 6.4 kg with lorcaserin, phentermine with topiramate, bupropion with naltrexone, and liraglutide, respectively. The most efficacious medication is phentermine with topiramate, but liraglutide has long-term evidence, up to 3 years, particularly in patient with prediabetes. A risk-benefit analysis should be completed to determine which specific medication should be initiated for a patient with type 2 diabetes and obesity.